2014
DOI: 10.1016/j.jchromb.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Determination of crizotinib in human and mouse plasma by liquid chromatography electrospray ionization–tandem mass spectrometry (LC-ESI–MS/MS)

Abstract: An LC-ESI-MS/MS method using high-throughput solid-phase extraction (SPE) was developed and validated to measure crizotinib in human and mouse plasma to support ongoing clinical and preclinical pharmacokinetic studies. Chromatographic separation of mouse or human plasma extracts was performed on a Supelco Discovery c18 column (50 × 2.1mm, 5.0 µ) with gradient elution using a combination of acidified aqueous and methanol (MeOH) mobile phases. The mass-to-charge transition monitored for detection and quantitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…These methods include, spectrofluorimetry, [3] spectrophotometry [4,5] and liquid chromatography-tandem mass spectrometry. [6][7][8] The use of nanotechnology in analytical chemistry field facilitates the evaluation and detection of pharmaceutical drugs in very small levels, increase the suitability of the analytical methods and cut down the cost of analytical analysis.…”
Section: Figure 1: Chemical Structure Of Crizotinibmentioning
confidence: 99%
“…These methods include, spectrofluorimetry, [3] spectrophotometry [4,5] and liquid chromatography-tandem mass spectrometry. [6][7][8] The use of nanotechnology in analytical chemistry field facilitates the evaluation and detection of pharmaceutical drugs in very small levels, increase the suitability of the analytical methods and cut down the cost of analytical analysis.…”
Section: Figure 1: Chemical Structure Of Crizotinibmentioning
confidence: 99%
“…The reproducibility is mostly affected by the repeated addition and elution of liquids, and can be corrected by the use of a preferably stable isotope labeled internal standard. While the most frequently stated reason for SPE in TKI bioanalysis is the reduced matrix effect compared to PP [15,[92][93][94], most papers do not state which factors influenced their choice for preparative methods. SPE provides clean samples, and can relatively easily be automated to in-line systems, but in-line SPE could drastically reduce sample throughput of the equipment.…”
Section: Solid-phase Extractionmentioning
confidence: 99%
“…With these steps, for normal size SPE columns, usually up to 1 ml per step is used. Micro-SPE column plates require less solvents, but still use 200 µl for washing and elution [15,92]. In TKI bioanalysis, SPE is mostly used for less sensitive and specific detection like UV [93,[96][97][98][99][100][101], or in multi-drug assays when short analytical run-times are desired [15], because there is not much space in the chromatography to accommodate ion-suppressive matrix components.…”
Section: Solid-phase Extractionmentioning
confidence: 99%
“…Accordingly, reliable and accurate analytical methodology for CRZ determination is crucial for further pharmacokinetic studies. Literature review revealed that CRZ was assayed in plasma by liquid chromatography coupled with either tandem mass spectrometry [6][7][8][9] or fluorescence detection [10]. However, these chromatographic methods suffered from complexity and being expensive.…”
Section: Introductionmentioning
confidence: 99%